Developing Highly Dimensionally Stable Multi-Layered Oriented Strand Board from Acacia Mangium Willd. Impregnated with Low Molecular Weight Phenolic Resin - Ong, Lay Lee (2002)
This study was carried out to investigate the effectiveness of pre-treatment of wood strands with low molecular weight phenol formaldehyde (LPF) resin to improve the dimensional stability of oriented strand board (OSB). The origin and extent of thickness swelling (TS) in OSB made from A. mangium Willd. were also investigated. Three- and five-layered OSBs were fabricated with 5% resin solid based on oven dry weight of wood strands (w/w) of phenol formaldehyde (PF) resin as a binder. The origin of TS was determined by using coating method where the edges and surfaces of the panel were coated with oil-based pigmented paint. To assess the degree of TS, the OSB specimens were sliced/sectioned into four layers through the thickness direction of the panel and were subjected to 24 hours of cold water soaking. The results showed that the water uptake by the panel occurred mainly through the four edges. The board surfaces absorbed 20% more water than those in the core. The distribution of TS and water absorption (WA) for the sectioned layers were found to resemble that of the vertical density profile of the OSB panel. The surface layers of the panel had relatively higher density, thus contribute significant influence over the TS of the board. The Pearson ratio showed a very high correlation between the board density and TS (R2 = 0.87 and 0.96 for three- and five-layered OSB, respectively). The untreated five-layered OSB (control) was found to be more stable than that of three-layered due to the presence of higher resin content in the surfaces (fine particles).